2018
DOI: 10.1021/acs.cgd.8b00015
|View full text |Cite
|
Sign up to set email alerts
|

Studies on CL-20/HMX (2:1) Cocrystal: A New Preparation Method and Structural and Thermokinetic Analysis

Abstract: A new preparation method for CL-20/HMX (2:1) cocrystal has been established at the laboratory level that is amenable for scale up. Solvent evaporation from a saturated solution of the stoichiometric mixture in the presence of a high boiling antisolvent, comparatively a very efficient and cheaper method, yielded pure cocrystals. Cocrystals were well characterized by spectroscopic, thermoanalytical tools, X-ray diffraction, and microscopic techniques. A correlation of percentage of cocrystal formation with evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 72 publications
2
49
1
Order By: Relevance
“…Encouraged by the great success of pharmaceutical co-crystallization, the development of new functional materials by co-crystallization techniques in other fields is attracting more and more interest. Nowadays, energetic cocrystallization has become very promising as an alternative method of tuning explosive structures and properties by rearranging existing molecules, instead of synthesizing new compounds (Ghosh et al, 2018;Sun et al, 2019). Another application of co-crystals is organic nonlinear optical materials with high second-order nonlinear susceptibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by the great success of pharmaceutical co-crystallization, the development of new functional materials by co-crystallization techniques in other fields is attracting more and more interest. Nowadays, energetic cocrystallization has become very promising as an alternative method of tuning explosive structures and properties by rearranging existing molecules, instead of synthesizing new compounds (Ghosh et al, 2018;Sun et al, 2019). Another application of co-crystals is organic nonlinear optical materials with high second-order nonlinear susceptibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent report, Mirnal Ghosh et al. reported the synthesis of EECC with CL‐20 and HMX having stoichiometric mixture 2 : 1 through solvent evaporation in presence of high boiling anti solvent and the authors observed better thermokinetic parameters with improved velocity of detonation and reduced sensitivity than CL‐20 . Zongwei Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cocrystallization has attracted interest in the field of energetic materials. Despite the lack of hydrogen bond donors in explosive molecules, some cocrystals of HEDMs were still obtained in a fortunate manner, such as benzotrifuroxan (Zhang, Guo et al, 2013), 1,3,5,7-tetranitro-1,3,5,7-tetraazacyclooctane (Shen et al, 2011;Li et al, 2015;Ghosh et al, 2018) and CL-20 (Bolton et al, 2011(Bolton et al, , 2012Yang et al, 2012;Huang et al, 2018). Cocrystallization yielded considerable improvement in the safety performance of HEDMs without a significant energy loss.…”
Section: Introductionmentioning
confidence: 99%